A novel blue excited white light emitting SrWO4: Pr3+ phosphor for single phase white-LED applications. Issue 20 (15th October 2022) - Gopal, Ram; Manam, Jairam
Abstract: A series of white light emitting Pr 3+ activated SrWO4 phosphors are synthesized by most facile solid state reaction routes. The structural properties are investigated by X-ray diffraction (XRD) spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), Energy dispersive X-ray (EDX) spectroscopy, Fourier transform infrared (FTIR) spectroscopy and X-ray photoemission spectroscopy (XPS). The optical properties are elaborated in detail using UV–visible–NIR spectroscopy and Photoluminescence (PL) spectroscopy. Rietveld refinement of obtained XRD data is performed to investigate the crystal structure and crystallographic parameters. The photoluminescence measurements ensure that the developed phosphors emit bright white light under UV excitation of 242 nm and blue excitation of 448 nm. The maximum emission intensity is achieved at 3 mol% doping of Pr 3+, followed by concentration quenching due to dipole-dipole interactions. The decay of electrons from the most populated 3 P0 state in all the samples follows the single exponential nature. The average decay time varies in the same manner as the emission intensity with Pr 3+ concentration. The color purities of the lights emitted from all the materials under 242 nm and 448 nm excitations are low (close to 10%) and hence suitable for white light. A bright white LED is successfully fabricated by coating the optimised phosphor SrWO4 : 3 mol% Pr 3+ on a 460 nm blue LED chip. The interesting results recommend that the proposed material can be used in developing single phase white-LED.